2022
DOI: 10.1051/0004-6361/202142951
|View full text |Cite
|
Sign up to set email alerts
|

Alma-Imf

Abstract: Aims. The processes that determine the stellar initial mass function (IMF) and its origin are critical unsolved problems, with profound implications for many areas of astrophysics. The W43-MM2&MM3 mini-starburst ridge hosts a rich young protocluster, from which it is possible to test the current paradigm on the IMF origin. Methods. The ALMA-IMF Large Program observed the W43-MM2&MM3 ridge, whose 1.3 mm and 3 mm ALMA 12 m array continuum images reach a ~2500 au spatial resolution. We used both the best-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 123 publications
1
18
0
Order By: Relevance
“…Column (3) in Table 4 shows the temperature used for each core in the mass estimation. We confirmed that the dust emission is optically thin by using Equation (B.2) from Pouteau et al (2022). We find that 99% of cores have an optical depth smaller than 0.04, and the maximum value is ∼0.1.…”
Section: Core Physical Parameterssupporting
confidence: 75%
“…Column (3) in Table 4 shows the temperature used for each core in the mass estimation. We confirmed that the dust emission is optically thin by using Equation (B.2) from Pouteau et al (2022). We find that 99% of cores have an optical depth smaller than 0.04, and the maximum value is ∼0.1.…”
Section: Core Physical Parameterssupporting
confidence: 75%
“…Moreover, we showed that using both the bsens and cleanest images (see definitions in Sect. 3.2), the number of robust core detections could further increase by a factor of up to ∼2 (companion paper: Paper III, Pouteau et al 2022). Extracting these additional sources requires careful treatment of the line contamination to exclude emission peaks associated with line rather than continuum emission.…”
Section: Population Of Cores In the Alma-imf Protoclustersmentioning
confidence: 99%
“…( 3)). According to Motte et al (2018b) and the companion paper, Paper III (Pouteau et al 2022), we estimate that about 20 cores (i.e., the most massive 3% of the core sample) could be partially optically thick. Therefore, their masses would be underestimated by factors of 15-40% when using Eq.…”
Section: Population Of Cores In the Alma-imf Protoclustersmentioning
confidence: 99%
“…In the DR21 cloud, the formation of high-mass stars would be directly related to the lifetime of the massive ridge. This potentially shorter phase of high-mass star formation might fit with the observed shallow slope of the core mass function (CMF) in high-mass star-forming regions (Liu et al 2018;Motte et al 2018b;Pouteau et al 2022) compared to the power-law tail of the initial mass function (IMF), as well as the slightly shallower IMFs in young clusters (< 4 Myr) of Cygnus X (Maia et al 2016). However, further work with, e.g., the ALMA-IMF sample (Motte et al 2022) will be needed to better understand the evolution of these topheavy CMFs in high-mass star-forming regions and how it connects with the IMF of young stellar clusters, as well as the evolution of high-mass star-forming clouds and filaments (Pouteau et al 2022).…”
Section: The Link With High-mass Star Formationmentioning
confidence: 73%